Identification of Multiple Genetic Susceptibility Loci in Takayasu Arteritis - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (CELL PRESS, 2013)
Takayasu arteritis is a rare inflammatory disease of large arteries. The etiology of Takayasu arteritis remains poorly understood, but genetic contribution to the disease pathogenesis is supported by the genetic association with HLA-B*52. We genotyped similar to 200,000 genetic variants in two ethnically divergent Takayasu arteritis cohorts from Turkey and North America by using a custom-designed genotyping platform (Immunochip). Additional genetic variants and the classical HLA alleles were imputed and analyzed. We identified and confirmed two independent susceptibility loci within the HLA region (r(2) < 0.2): HLA-B/MICA (rs12524487, OR = 3.29, p = 5.57 x 10(-16)) and HLA-DQB1/HLA-DRB1 (rs113452171, OR = 2.34, p = 3.74 x 10(-9); and rs189754752, OR = 2.47, p = 4.22 x 10(-9)). In addition, we identified and confirmed a genetic association between Takayasu arteritis and the FCGR2A/FCGR3A locus on chromosome 1 (rs10919543, OR = 1.81, p = 5.89 x 10(-12)). The risk allele in this locus results in increased mRNA expression of FCGR2A. We also established the genetic association between IL12B and Takayasu arteritis (rs56167332, OR = 1.54, p = 2.18 x 10(-8)).
Keywords: GENOME-WIDE ASSOCIATION; GIANT-CELL ARTERITIS; ULCERATIVE-COLITIS; MYCOBACTERIUM-TUBERCULOSIS; HLA ALLELES; POPULATION; DISEASE; TURKEY; VISUALIZATION; HAPLOTYPES